2018
DOI: 10.1002/cam4.1729
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cell‐like characteristics and telomerase activity of the nasopharyngeal carcinoma radioresistant cell line CNE‐2R

Abstract: The radioresistance of nasopharyngeal carcinoma (NPC) may be related to cancer stem cells (CSCs), and the characteristics of CSCs may be maintained by telomerase activity. In this study, we explored the CSC‐like characteristics and telomerase activity of the NPC radioresistant cell line CNE‐2R. This work provides a foundation for future studies on stem cell‐targeted therapies by targeting the radioresistance of NPC. The expression of stem cell‐related genes/proteins and the hTERT gene/protein in CNE‐2R and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…[9][10][11] In previous research, we found that CNE-2R cells also displayed CSC-like traits and a high level of telomerase activity. 12 Telomerase activity is closely related to CSCs, 15,16 which is considered to be essential for CSCs to progress, self-renew, and immortalize. 17 hTERT is an indispensable catalytic subunit to maintain the telomerase activity, which can regulate the telomerase activity at the transcription level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] In previous research, we found that CNE-2R cells also displayed CSC-like traits and a high level of telomerase activity. 12 Telomerase activity is closely related to CSCs, 15,16 which is considered to be essential for CSCs to progress, self-renew, and immortalize. 17 hTERT is an indispensable catalytic subunit to maintain the telomerase activity, which can regulate the telomerase activity at the transcription level.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, we discovered that the radioresistant NPC cell line CNE-2R displayed CSC-like traits and a high level of telomerase activity, as well as highly expressed human telomerase reverse transcriptase (hTERT). 12 Due to strict transcriptional suppression of the hTERT gene, telomerase activity is absent in most normal human somatic cells. 13 However, expression of hTERT and telomerase activity can be observed in as high as 90% of human malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased mTERT (mouse) expression can accelerate skin wound healing and promote carcinogenesis without affecting telomere length [ 17 ]. Forced expression of telomerase can modify the inner functions of stem cells [ 18 ].…”
Section: Telomerasementioning
confidence: 99%
“…The absorbance was measured in triplicate at 450 nm, by reading against a blank (reference absorbance at 690 nm). Samples were regarded as telomerase-positive if the difference in absorbance (A 450 − A 690 ) was greater than 0.2 [49,50].…”
Section: Telomerase Activity Assaymentioning
confidence: 99%